Administration of platelet concentrates suspended in bicarbonated Ringer's solution in children who had platelet transfusion reactions. Issue 2 (25th October 2017) - Kobayashi, J.; Yanagisawa, R.; Ono, T.; Tatsuzawa, Y.; Tokutake, Y.; Kubota, N.; Hidaka, E.; Sakashita, K.; Kojima, S.; Shimodaira, S.; Nakamura, T.
Abstract : Background and Objectives: Adverse reactions to platelet transfusions are a problem. Children with primary haematological and malignant diseases may experience allergic transfusion reactions (ATRs) to platelet concentrates (PCs), which can be prevented by giving washed PCs. A new platelet additive solution, using bicarbonated Ringer's solution and acid–citrate–dextrose formula A (BRS‐A), may be better for platelet washing and storage, but clinical data are scarce. Materials and Methods: A retrospective cohort study for consecutive cases was performed between 2013 and 2017. For 24 months, we transfused washed PCs containing BRS‐A to children with primary haematological and malignant diseases and previous adverse reactions. Patients transfused with conventional PCs (containing residual plasma) were assigned as controls, and results were compared in terms of frequency of ATRs, corrected count increment (CCI) and occurrence of bleeding. We also studied children transfused with PCs washed by a different system as historical controls. Results: Thirty‐two patients received 377 conventional PC transfusions. ATRs occurred in 12 (37·5%) patients from transfused with 18 (4·8%) bags. Thirteen patients, who experienced reactions to regular PCs in plasma, then received 119 transfusion bags of washed PCs containing BRS‐A, and none had ATRs to washed PCs containing BRS‐A. Before study period, six patients transfused 137 classical washed PCs with different platelet additive solution, under same indication, ATRs occurred in one (16·7%) patient from transfused with one (0·7%) bags. CCIs (24 h) in were lower with classical washed PCs (1·26 ± 0·54) compared to regular PCs in plasma (2·07 ± 0·76) ( P  < 0·001), but there was no difference between washed PCs containing BRS‐A (2·14 ± 0·77) and regular PCs (2·21 ± 0·79) ( P  = 0·769), and we saw no post‐transfusion bleeding. Conclusion: Washed PCs containing BRS‐A appear to prevent ATRs without loss of transfusion efficacy in children with primary haematological and malignant diseases. Their efficacy should be further evaluated through larger prospective clinical trials.